A Rare Case Report of Duodenal Adenocarcinoma Accompanied by Cerebellar Medulloblastoma - Afaghi, Siamak; Khoshpour, Nastaran; Hosseini, Amirhossein; Esmaeili Tarki, Farzad; Sadat Rahimi, Fatemeh; Nilipour, Yalda; Dara, Naghi; Imanzadeh, Negar (Student Research in Translational Medicine, 2020)
A case of a 6-year-old female with a diagnosis of Duodenal Adenocarcinoma is presented by the authors, in which 24 months subsequent to undergoing radiation therapy for a Cerebellar Medulloblastomas, the mentioned diagnosis has been confirmed. Although, the chance of a secondary malignancy has been recognized to be elevated in children formerly undergone radiation therapy, the incidence of duodenal adenocarcinoma is a highly infrequent condition. As a consideration, observing manifestations like weight loss, vomiting, and icterus in a pediatric patient who has been administered earlier on with radiation therapy, must alert physicians that the risk of a gastrointestinal malignancy exists.